Removing leakage-induced correlated errors in superconducting quantum error correction - M. McEwen (Nature Portfolio, 2021)
Correlated errors coming from leakage out of the computational subspace are an obstacle to fault-tolerant superconducting circuits. Here, the authors use a multi-level reset protocol to improve the performances of a bit-flip error correcting code by reducing the magnitude of correlations.